Implementasi Peraturan Pengangkutan Laut dalam Mensikapi Petikemas yang Berwawasan Kemaritiman - Tugino, Tugino; Harini, Harini (Marine Science and Technology Journal, 2024)
Working Law number 17 of 2008 is a reference for sea transportation in relation to containers and as an archipelagic country that has vast seas and long coastlines, the maritime and maritime sectors are very strategic for Indonesia in terms of the economic and environmental aspects which are suitable for sea transportation for Container: The definition of a container is a tool for transporting goods in whole/in part/closed form so that it takes the form of a crate or crate and is intended to be filled with the goods to be transported. In order to promote non-oil and gas exports, the Government through the Department of Transportation has taken several important and strategic steps in its involvement in achieving the goal of procuring container ships so as to smooth and stabilize the foreign trade balance, in addition to obtaining reasonable cargo. Moreover, in this era of containerization, it is not enough to just build a port, but it also needs to be supported by personnel in the field, work systems and procedures as well as suggestions and other infrastructure that are in accordance with the value and benefits of the container itself.